2D porous molybdenum nitride/cobalt nitride heterojunction nanosheets with interfacial electron redistribution for effective electrocatalytic overall water splitting. Issue 13 (15th March 2021) - Guo, Hao; Wu, Aiping; Xie, Ying; Yan, Haijing; Wang, Dongxu; Wang, Lei; Tian, Chungui
Abstract : Porous 2D Mo2 N-Co x N heterojunction nanosheets have been constructed based on a new strategy of cutting ZIF-67 polyhedral in Na2 MoO4 aqueous solution. The material can act effective bi-functional catalysts for overall water splitting. Abstract : Binary transition metal-based nitrides are promising for overall water splitting. Morphology and heterojunction engineering is important to realize effective catalysis, but their simultaneous engineering remains a challenge. Herein, we have shown the designed synthesis of porous 2D molybdenum nitride/cobalt nitride heterojunction nanosheets (2D porous Mo2 N–Co x N) based on controllable nitridation of Mo species modified Co(OH)2 (Co–Mo–O) nanosheets by cutting ZIF-67 polyhedra in Na2 MoO4 aqueous solution. The combined advantages, including the favourable water dissociation kinetics due to the electron redistribution at the heterointerface as shown by theoretical calculations, the large accessible surface of the nanosheets and enhanced mass-transport ability of pores, endow the 2D porous Mo2 N–Co x N with excellent electrocatalytic HER activity with a low overpotential at a current density of 10 mA cm −2 ( η 10 of 29 mV, close to that of Pt/C) and good OER performance with η 10 of 247 mV. An electrolyzer based on the 2D porous Mo2 N–Co x N electrodes only needs 1.53 V to reach a current density of 10 mA cm −2, and can be driven by a solar panel. The strategy is versatile and can be used to prepare other 2D heterojunction catalysts, such as W (V)–Co based catalysts.